Construction and Verification of Immunohistochemistry Parameters-Based Classifier to Predict Local-Recurrence of Upper Tract Urothelial Carcinoma After Kidney-Sparing Surgery - Cheng, Xu; Liu, Wentao; Li, Yijian; Wang, Yinhuai (Frontiers in Oncology, 2022)
Background: Kidney-sparing surgery (KSS) for upper tract urothelial carcinomas (UTUCs) has been gradually performed in selected patients beyond the recommendation of guidelines. However, there is still a lack of tools to evaluate postoperative local recurrence. Herein, a new nomogram was established to predict the local recurrence risk after KSS. Methods: Patients were randomly divided into two cohorts (training: testing cohorts = 7:3). Cancer samples after KSS were used for immunohistochemical tests to detect molecules missing in previous pathology reports. Then, the total number of molecules were screened by the least absolute shrinkage and selection operator (LASSO) method to construct an IHCscore, which was further tested in the validation cohort. Finally, the IHCscore and other clinicopathologic parameters were combined to develop a more accurate model using univariate and multivariate Cox regression methods. Results: In total, 200 patients were included. The Kaplan–Meier test showed that high Ki-67 and loss of Uroplakin III and E-cadherin were correlated with poor recurrence-free survival. The individual IHCscore was calculated based on the expression levels of Ki-67, Her2 and E-cadherin. Based on the IHC score, patients were further classified as low- or high-risk, and a significant difference in the recurrence-free survival was observed between the two groups. Then, the nomogram was developed based on Gender, surgical margin and IHCscore; this nomogram had a higher AUC (0.847) in predicting 3-year recurrence-free survival than the IHCscore alone (0.788). Conclusions: This easy-to-use nomogram shows better prediction accuracy in recurrence-free survival after KSS and may guide individualized intravesical chemotherapy. However, a larger sample is required for external validation.